Phase transition, mechanical, dielectric and piezoelectric properties of perovskite (Pb1-xBax)ZrO3ceramics - Naratip Vittayakorn (2018)
(Pb1-xBax)ZrO3ceramics were prepared in the composition range 0.00≤x≤0.30 by the mixed oxide solid-state reaction method. The samples were kept at the calcination temperature 1000 °C for 1 h and at the sintering temperature 1300 °C for 3 h. The structural phase transitions and the dielectric properties were studied. It was found that the density of the ceramics decreases with increasing amount of Ba2+, whilst the average grain size is in the range 1-2.3 μm. The structure of as-calcined powder reveals that the fraction of the orthorhombic phase is decreasing with increasing Ba2+content. The values of Vickers and Knoop hardness are in the range of 4.10-6.48 and 4.15-5.67 GPa, respectively. Dielectric measurements show that the antiferroelectric phase (AFE)-ferroelectric phase (FE) and the FE to paraelectric phase (PE) phase transformation temperatures decrease with increasing Ba2+concentration. The AFE-FE phase transformation is detected for compositions 0.00≤x≤0.075. The maximum dielectric constant gradually increases with increasing composition up to x=0.20. For higher Ba2+concentrations, the lowering of the maximum dielectric value is accompanied by a progressive broadening of the permittivity peak. The d33values of the samples increase from ∼0 to 87 pC/N with increasing Ba2+concentration from x=0.00 to 0.30. © 2006 Elsevier B.V. All rights reserved.